2016
DOI: 10.7150/thno.13580
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Stabilization of a Gastrin-Releasing Peptide Receptor Antagonist Enhances PET Imaging and Radionuclide Therapy of Prostate Cancer in Preclinical Studies

Abstract: A single tool for early detection, accurate staging, and personalized treatment of prostate cancer (PCa) would be a major breakthrough in the field of PCa. Gastrin-releasing peptide receptor (GRPR) targeting peptides are promising probes for a theranostic approach for PCa overexpressing GRPR. However, the successful application of small peptides in a theranostic approach is often hampered by their fast in vivo degradation by proteolytic enzymes, such as neutral endopeptidase (NEP). Here we show for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
52
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 42 publications
7
52
1
1
Order By: Relevance
“…As expected, the uptake in GRPR‐expressing organs was also significantly increased, while the uptake in nontarget healthy tissues, particularly the kidneys were not affected. This strategy has been successfully used to enhance the efficacy of other peptide‐based targeting vectors …”
Section: Discussioncontrasting
confidence: 99%
“…As expected, the uptake in GRPR‐expressing organs was also significantly increased, while the uptake in nontarget healthy tissues, particularly the kidneys were not affected. This strategy has been successfully used to enhance the efficacy of other peptide‐based targeting vectors …”
Section: Discussioncontrasting
confidence: 99%
“…Consequently, lower tumor uptake was achieved in mice, a handicap that could be reversed by in situ neutral endopeptidase inhibition with phosphoramidon (24). However, this promising approach, recently shown to improve the theranostic potential of other GRPR radioantagonists as well, has not yet been translated in humans (22).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that noninternalizing radioantagonists can successfully target and be sufficiently retained in GRPR-expressing cancer lesions while rapidly clearing from physiologic organs in both animal models and humans. The superior pharmacokinetics of GRPR radioantagonists over their agonist counterparts in combination with their higher inherent biosafety has shifted current research toward the design of new improved GRPR radioantagonist candidates with clear potential for clinical translation (19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, dosimetry calculations resulted in a 1.3-timeshigher tumor dose and a 5-times-lower pancreas dose with 200 pmol 177 Lu-NeoBOMB1 than 10 pmol 177 Lu-NeoBOMB1. When dosimetry data are compared with other radiolabeled GRPR antagonists, such as 177 Lu-JMV4168 (29), estimated absorbed radiation doses to the tumor were higher for 177 LuNeoBOMB1 (29 Gy/50 MBq vs. 11 Gy/50 MBq) even when 177 Lu-JMV4168 was stabilized by coinjection of an enzyme inhibitor (29 Gy/50 MBq vs. 20 Gy/MBq). When we compared the dose to the kidneys and pancreas of the radiotracers, we found a more favorable tumor-to-kidney ratio for 177 LuNeoBOMB1 (10 vs. 1.5) and a similar tumor-to-pancreas ratio (2.2 vs. 2.5).…”
Section: Discussionmentioning
confidence: 99%